Toward the Charter: Canadians and the Demand for a National Bill of Rights, 1929-1960 - Clément, Dominique (Labour / Le Travail, 2004)
The article reviews the book, "Toward the Charter: Canadians and the Demand for a National Bill of Rights, 1929-1960," by Christopher MacLennan.